1996
DOI: 10.1007/s004010050488
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of β-amyloid precursor protein and ubiquitin in axons after spinal cord trauma in humans: immunohistochemical observations on autopsy material

Abstract: We evaluated by immunohistochemistry the presence of beta-amyloid precursor protein (beta APP) and ubiquitin-like material which may accumulate in axons of the human spinal cord subjected to injury. Autopsy material was obtained from nine cases with different types of trauma: breech delivery with neonatal spinal injury, compression of the cord induced by fractures of the vertebral column, haematomas or intradural meningioma. The posttrauma period ranged from 10 days to several years. The spinal cord of six con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Secondary injury mechanisms include inflammation and reactive astrogliosis and microglial activation, which are involved in scar formation and impaired regeneration (Lu et al, 2000). Among the biochemical changes are increases in APP, its secretases, and Aβ shown in this and other studies of human and rat tissues (Ahlgren et al, 1996; Choo et al, 2008; Cornish et al, 2000; Kobayashi et al, 2010; Li et al, 1995). …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Secondary injury mechanisms include inflammation and reactive astrogliosis and microglial activation, which are involved in scar formation and impaired regeneration (Lu et al, 2000). Among the biochemical changes are increases in APP, its secretases, and Aβ shown in this and other studies of human and rat tissues (Ahlgren et al, 1996; Choo et al, 2008; Cornish et al, 2000; Kobayashi et al, 2010; Li et al, 1995). …”
Section: Discussionsupporting
confidence: 67%
“…We recently demonstrated that inhibiting the activity of APP secretases and Aβ is protective in a mouse model of TBI (Loane et al, 2009), suggesting that Aβ may be contributing to secondary injury cascades after TBI. APP is also increased after spinal cord injury (SCI), in both humans and rodents (Ahlgren et al, 1996; Choo et al, 2008; Cornish et al, 2000; Li et al, 1995). A recent study in rats shows that the increase in APP and PS1 is accompanied by an increase in Aβ peptide levels as early as 1 day after spinal cord hemisection.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the YA cohort poses some specific challenges because these individuals died as the result of severe trauma and there was no additional information concerning their post-traumatic clinical course. Therefore, the mean holoAPP molecular levels observed in the YA Pc and PCG regions may represent a response to severe brain concussion as has been reported for acute traumatic brain injury with axonal damage [98][101].…”
Section: Discussionmentioning
confidence: 66%
“…47 Spinal cord injury induces accumulation of β-amyloid precursor protein and β-amyloid peptide in the injured spinal cord, which is associated with the neurodegenerative processes of aging motor neuron. 47,48 Reactive oxygen species (ROS) that can induce DNA damage and accelerate cellular senescence are upregulated in the damaged neural tissue after SCI. [49][50][51][52] Recent studies revealed that an inhibition of mTOR decelerates cellular senescence and increases the lifespan in diverse organisms.…”
Section: Suppression Of Cellular Senescence and Organismalmentioning
confidence: 99%